Trends and perspectives in polymer science and technology : - Pirozzi, B. (Wiley-VCH, 2006)
This book contains contributions to the Symposium of the Italian Macromolecules Science and Technology Association (AIM). This conference, which takes place every two years in various Italian cities, represents the most important gathering for the AIM members. The 17th AIM Symposium held in Naples in 2005 celebrated the 30th AIM anniversary. The symposium covered the following topics: Synthesis and modifications of polymers; structure, properties and macromolecular architecture; polymers for biomedical applications; functional polymers and polymers for special uses; biopolymers.